Developing the Management Competencies for Getting a Competitive Position in the Organic Food Market - Năstase, Marian; Stoian, Mirela; Ion, Raluca Andreea (Revista de Management Comparat International, 2011)
Although almost any conference tackles the issue of organic foods, we consider that this article does not fit into normal patterns of research. Our paper proposes a complex analysis in the field of organic food products. It also highlights the need of developing new competences of managers and marketers in analysing market for getting a competitive position on it. The method used is the Six Thinking Hats, devised by Edward de Bono. This method appeals to the driving creative thinking; it can be applied in almost any field of analysis. The outcomes show that, using creative thinking, the leaders develop new competences which enable them to better analyse organic food market and to identify and gain competitive positions on it.